Characteristics of second-order residual ionospheric error in GNSS radio occultation and its impact on inversion of neutral atmospheric parameters. (August 2015) - Qu, Xiaochuan; Li, Zhenghang; An, Jiachun; Ding, Wenwu
Abstract: In Global Navigation Satellite Systems (GNSS) radio occultation (RO), one of the most significant error sources is the ionospheric error, which is largely eliminated by dual-frequency linear combination. However, second-order residual ionospheric error (RIE) in excess phase still remains and affects the retrievals of neutral atmospheric parameters in RO. Second-order RIE varies with RO azimuth in a sinusoidal pattern for a set of simulated RO events occurring in the same location at different azimuths. The amplitude of the sinusoidal curve below 60 km is at the order of sub-centimeter under moderate solar activity level. The retrieval biases of the neutral atmospheric parameters induced by second-order RIE also have sinusoidal features with RO azimuth, but have opposite variation trends to that of the second-order RIE. The RO azimuths of the maximum positive and negative retrieval biases correspond approximately to the azimuths of maximum negative and positive second-order RIEs, respectively. The order of the maximum bending angle bias induced by the second-order RIE is about 10 −8  rad under moderate solar activity level. However, the retrieval errors at low latitude are larger than those at high and middle latitudes, and the maximum temperature bias at low latitude could be 0.35 K at 40 km. Based on the sinusoidal variation of second-order RIE, it is shown that even at the same RO point and under the same solar activity level, the second-order RIEs at different RO azimuths still have different effects on the retrieval precision of atmospheric parameters. This should be considered carefully when many RO profiles are averaged for climate trend detection, especially at low latitude. Highlights: Considering RO azimuth, we quantify second-order RIE and its effects accurately. The maximum RIE and the biases of atmospheric parameters occur at RO azimuth 180 ° and 0 ° . The RO second-order RIE below 60 km is at the order of sub-centimeter (F10.7=150 sfu). The temperature bias at 40 km can reach to about 0.35 K at low latitude (F10.7=150 sfu).